2007
DOI: 10.1136/oem.2006.028100
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumours and exposure to pesticides: a case–control study in southwestern France

Abstract: Background: Brain tumours are often disabling and rapidly lethal; their aetiology is largely unknown. Among potential risk factors, pesticides are suspected. Objective: To examine the relationship between exposure to pesticides and brain tumours in adults in a population-based case-control study in southwestern France. Methods: Between May 1999 and April 2001, 221 incident cases of brain tumours and 442 individually matched controls selected from the general population were enrolled. Histories of occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 20 publications
3
49
0
1
Order By: Relevance
“…A possible explanation for this discrepancy may lie in the aging populations in developed countries. 9 The mean age of patients with neuroepithelial tumors in our study was 39.38 years, compared to that measured in Korea, 43.5 years. 10 The mean age of patients diagnosed with meningiomas in one European report was 57.6 years, in an American report: 59 years and in an Asian report : 58.1 years.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A possible explanation for this discrepancy may lie in the aging populations in developed countries. 9 The mean age of patients with neuroepithelial tumors in our study was 39.38 years, compared to that measured in Korea, 43.5 years. 10 The mean age of patients diagnosed with meningiomas in one European report was 57.6 years, in an American report: 59 years and in an Asian report : 58.1 years.…”
Section: Discussionmentioning
confidence: 83%
“…12 Provost et al, suggested the possible explanation for a higher frequency of gliomas in males may be due to specific occupational exposures. 9 Possible reasons for the observed gender variations may arise as a result of possible variabilties in the susceptibility of X and Y chromosomes to tumorigenic stimuli, while others postulate a protective effect of female sex hormones against brain tumors. 19 A review of data obtained from the SEER program suggested a higher incidence of meningiomas in females…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A link between exposure to pesticides and increased risk of brain tumours has been hypothesized (Khuder et al, 1998;Lee et al, 2005;Provost et al, 2007). Pesticide exposure was not included in the INTEROCC study as FINJEM only provides exposure estimates for fungicides, herbicides, and insecticides rather than (categories of) active ingredients.…”
Section: Exposuresmentioning
confidence: 99%
“…We briefly summarize here the methods decribed in a previous paper. 13 Eligible cases were all subjects aged 16 years and over, newly diagnosed with a brain tumor during the period from May 1, 1999 to April 30, 2001 and living in Gironde when diagnosed. Topography codes for primary brain tumors following the International Classification of Diseases for Oncology third edition (ICD-O-3) were included in the study: C70.0-C70.9 (meninges), C71.0-C71.9 (brain) and C72.2-C72.9 (cranial nerves and other parts of the CNS).…”
Section: Study Subjectsmentioning
confidence: 99%